2012
DOI: 10.1089/jop.2011.0141
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Assessment of Optic Nerve and Retinal Functions Following Intravitreal Injection of Bevacizumab (Avastin)

Abstract: Intravitreal bevacizumab did not appear to be toxic to the retina or the optic nerve at a concentration of 1.25 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
0
14
0
5
Order By: Relevance
“…The effects of macular diseases on VEP are well established (Marcus et al 1983;Folk et al 1984;Bass et al 1985;Sherman et al 1986;Johnson et al 1987;Shimada et al 1997;Sabeti et al 2013), but there are only few previous studies where patients are treated for wet AMD and the possible modulation of their VEP is followed (Macky & Mahgoub 2012). In our previous study, we have shown that beneficial anti-VEGF injections of wet AMD patients improve the VEP markers (Vottonen et al 2013).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The effects of macular diseases on VEP are well established (Marcus et al 1983;Folk et al 1984;Bass et al 1985;Sherman et al 1986;Johnson et al 1987;Shimada et al 1997;Sabeti et al 2013), but there are only few previous studies where patients are treated for wet AMD and the possible modulation of their VEP is followed (Macky & Mahgoub 2012). In our previous study, we have shown that beneficial anti-VEGF injections of wet AMD patients improve the VEP markers (Vottonen et al 2013).…”
Section: Introductionmentioning
confidence: 87%
“…; Sabeti et al. ), but there are only few previous studies where patients are treated for wet AMD and the possible modulation of their VEP is followed (Macky & Mahgoub ). In our previous study, we have shown that beneficial anti‐VEGF injections of wet AMD patients improve the VEP markers (Vottonen et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive and/or negative effects on face processing of the now routine injection treatments have been largely overlooked. There are only 2 groups that have assessed visual evoked potentials (VEP) of wet AMD patients after anti-VEGF injections; reports including 2 of ours, with the key finding of increase in VEP amplitude 2830. The electrophysiological parameters of face detection in this context have not been reported earlier.…”
Section: Discussionmentioning
confidence: 84%
“…The effects of AMD and its current treatment in any specific cortical visual processes have been only occasionally studied 2830. Individual patient investigations using functional MRI analysis have examined the reorganization in the visual cortex caused by AMD 31,32.…”
Section: Discussionmentioning
confidence: 99%
“…Since no VEP changes toward the same direction were observed in the nontreated eye, the finding supports the concept that improved peripheral input plays a significant role in the neural plasticity of the visual cortex. In order to confirm these findings, larger population studies are required, and functional technological analyses are needed 11,12…”
Section: Discussionmentioning
confidence: 99%